Aflatoxins: - Wacoo, Paul Alex; Atukunda, Prudence; Muhoozi, Grace; Braster, Martin; Wagner, Marijke; Broek, J van den Tim; Sybesma, Wilbert; Westerberg, C. Ane; Iversen, Ole Per; Kort, Remco (MDPI, 2020)
Chronic exposure of children in sub-Saharan Africa to aflatoxins has been associated with low birth weight, stunted growth, immune suppression, and liver function damage. Lactobacillus species have been shown to reduce aflatoxin contamination during the process of food fermentation. Twenty-three Lactobacillus strains were isolated from fecal samples obtained from a cohort of rural Ugandan children at the age of 54 to 60 months, typed by 16S rRNA gene sequencing, and characterized in terms of their ability to bind aflatoxin B1 in vitro. Evidence for chronic exposure of these children to aflatoxin B1 in the study area was obtained by analysis of local foods (maize flour and peanuts), followed by the identification of the breakdown product aflatoxin M1 in their urine samples. Surprisingly, Lactobacillus in the gut microbiota of 140 children from the same cohort at 24 and 36 months showed the highest positive correlation coefficient with stunting among all bacterial genera identified in the stool samples. This correlation was interpreted to be associated with dietary changes from breastfeeding to plant-based solid foods that pose an additional risk for aflatoxin contamination, on one hand, and lead to increased intake of Lactobacillus species on the other. Keywords: Stunting; aflatoxin B1; Lactic acid bacteria; aflatoxin binding; gut microbiota
Occurrence, Exposure, and Binding to Lactobacillus Species from the Gut Microbiota of Rural Ugandan Children
Article